Free Schooling Reverses Sibling Rivalry - Jo\~ao R. Ferreira; Wayne Aaron Sandholtz (Institute of Labor Economics (IZA), 2024)
We use administrative data to measure sibling spillovers on academic performance before and after Tanzania's introduction of Free Secondary Education (FSE). Prior to FSE, students whose older siblings narrowly passed the secondary school entrance exam were less likely to go to secondary school themselves; with FSE, the effect became positive. Negative spillovers in the pre-reform period were concentrated in poorer regions; positive spillovers in the post-reform period were largest for lower-performing younger siblings. This suggests that FSE alleviated financial constraints, allowing families to distribute educational investments more equitably rather than concentrating resources on high-performing children.
Keywords: D10; I20; I25; J13; 330; sibling spillovers; educational achievement; resource constraints; high-stakes exams